What makes the difference between unsuccessful and successful firms in the German mechanical engineering industry? A microsimulation approach using data from the NIFA-Panel - Ulrich Widmaier; Hiltrud Niggemann; Joachim Merz (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1994)
Against a background of rising costs and increasing competition, it is becoming more and more difficult for the small and medium-sized firms of the German mechanical engineering industry to be economically successful. The thesis that rapidly changing markets, products and production processes cause serious economic problems for these firms is, however, a proposition on an average trend. A substantial number of firms are not only capable of coping with these conditions and challenges, but are even able to expand their business activities, including employment. We may hypothesize that their product and market strategies as well as their internal mode of operation and organization differs significantly from those firms doing economically less well. In order to test the significance of factors which could lead to different levels of success, operationalized with data of the NIFA panel the method of static microsimu lation is applied using the program MICSIM. This particular method offers the possibility of reweighting the information contained in micro datasets according to restrictions given by aggregated data (i.e. marginal distributions). The latter will be chosen in such a way that the number of firms with properties (strategies), hypothetically leading to success in terms of lower excess capacity, are - artificially - increased in the sample. The research goal is to find out whether such hypothetical strategies are supported by the data. The basic finding that certain complex strategies are more often successful demonstrates that unidimensional approaches to modernize production are of less value. Only in those strategies wehere organization of production, technical equipment, degree of vertical integration, products and customers are part of an intergrated innovational strategy, is success most likely to be fuelled. – – Angesichts steigender Kosten und sich verschärfenden Wettbewerbs wird es für die vorwiegend mittelständisch strukturierten Betriebe des deutschen Maschinenbaus immer schwieriger, wirtschaftlich erfolgreich zu sein. Allerdings ist die These von zunehmenden Wettbewerbs- und damit wirtschaftlichen Problemen eine Aussage über den durchschnittlichen Trend. Es gibt eine erhebliche Anzahl von Betrieben, die diesen Bedingungen und Herausforderungen nicht nur trotzen, sondern sogar ihre geschäftlichen Aktivitäten einschließlich der Zahl der Beschäftigten ausweiten. Die Hypothese scheint naheliegend, daß sich ihre Produkt- und Marktstrategien sowie ihre internen Strukturen von denen der weniger erfolgreichen Betrieben signifikant unterscheiden.Die Überprüfung der Faktoren, die zu unterschiedlichem Erfolg führen könnten, wird mit den Daten des NIFA Panels und der Methode der statischen Mikrosimulation unter Verwendung des Programms MICSIM vorgenommen. Diese Methode erlaubt es insbesondere, die Information des Mikrodatensatzes gemäß der Restriktionen aus aggregierten Daten umzugewichten. Die Hochrechnung wird so angewendet, daß die Anzahl der Betriebe mit hypothetisch erfolgreichen Strategien gemessen an geringerem Kapazitätsüberschuß durch Umgewichtung in der Stichprobe vergrößert wird. Es wird dann untersucht, ob solche hypothetischen Strategien von den Daten getragen werden.Das Hauptergebnis, daß komplexe Strategien häufiger erfolgreich sind, deutet auf die zunehmende Problematik eindimensionaler Lösungen zur Erzielung betrieblicher Erfolge hin. Vor allem, wenn Fertigungstiefe, Fertigungsorganisation, Produkte und Märkte in eine ganzheitliche Innovationsstrategie eingebunden werden, stellt sich der Erfolg meist ein.
Keywords: C80; C81; J20; M13; M21; 330; economic succes; NIFA PANEL; microsimulation; engineering; Wirtschaftlicher Erfolg; NIFA PANEL; Mikrosimulation; Maschinenbau; Maschinenbau; Wettbewerbsstrategie; Erfolgsfaktor; Panel; Deutschland